1979
DOI: 10.1016/0039-6028(79)90093-1
|View full text |Cite
|
Sign up to set email alerts
|

Structure determination of the reconstructed Au(110) surface

Abstract: The LEED pattern of the Au( 110) surface shows a (1 X 2) and also a (1 X 3) superstructure.The (1 X 2) superstructure has been determined by comparison of LEED intensities with model calculations. The missing row model is the most probable model. A miniium of the averaged F-factor, F = 0.36, has been found for 15% contraction of the first layer spacing without atomic displacements in the second layer.The clean (110) faces of gold are known to exhibit a reconstruction of the atomic arrangement in the surface la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(44 citation statements)
references
References 8 publications
0
43
1
Order By: Relevance
“…II A͒, our calculations still indicate a preference for reconstruction, which is in agreement with experiments. [4][5][6][7][8][9][10]32,34 In these experiments it was also observed that at elevated temperatures and an oxygen partial pressure of 5 ϫ 10 −11 atm there is coexistence of different reconstructed surfaces. This is also supported by our calculations, since the stability of the three reconstructed surfaces differs only by 1 -3 meV/ Å 2 , which is within the inaccuracy of the calculations.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…II A͒, our calculations still indicate a preference for reconstruction, which is in agreement with experiments. [4][5][6][7][8][9][10]32,34 In these experiments it was also observed that at elevated temperatures and an oxygen partial pressure of 5 ϫ 10 −11 atm there is coexistence of different reconstructed surfaces. This is also supported by our calculations, since the stability of the three reconstructed surfaces differs only by 1 -3 meV/ Å 2 , which is within the inaccuracy of the calculations.…”
Section: Resultsmentioning
confidence: 60%
“…While 3d and 4d metals, such as Cu͑110͒, Ag͑110͒, or Pd͑110͒, preferentially reconstruct after adsorption of alkali metals ͑e.g., Na, K or Cs͒, [1][2][3] 5d metals, such as Au͑110͒, Pt͑110͒, or Ir͑110͒, reconstruct already in their clean states. [4][5][6][7][8][9][10] In contrast to clean Au͑110͒ and Pt͑110͒ surfaces, which show a ͑1 ϫ 2͒-missing-row reconstruction, [11][12][13][14][15][16][17] the situation is more complex for Ir͑110͒ and a variety of potential surface structures have been reported. Here the strong tendency towards stable ͕111͖ microfacets and nanofacets seems to be the driving force for different surface reconstructions, trying to minimize the overall surface free energy.…”
Section: Introductionmentioning
confidence: 99%
“…Though the previous structural results obtained by low energy electron diffraction (LEED) intensity analysis were somewhat unsatisfactory [3][4][5][6], a preference for the missing row model was always found. Most other models could be excluded by ion scattering studies [7][8][9][10][11].…”
mentioning
confidence: 87%
“…The missing row model is consistent with the results of most other methods applied to the (110) faces of Pt, Ir and Au. All three faces are believed to exhibit the same reconstruction [3][4][5][6][7][8][9][10][11].…”
mentioning
confidence: 99%
“…The principal structural feature is that every other row of close-packed atoms along the 11 0 [ ] direction is missing, thereby doubling the unit cell in the 001 [ ] direction [22]. Also, this surface exhibits an oscillatory relaxation, with a contraction in the first-second layer spacing, and a slight expansion in the second-third layer spacing.…”
Section: Clean Au(110)-(2×1)mentioning
confidence: 99%